Heteronuclear NMR of DNA with the heteronucleus in natural abundance: facilitated assignment and extraction of coupling constants. - Schmieder, P (1992)
Two heteronuclear proton-carbon NMR experiments are applied to the DNA-octamer d(TTGGCCAA)2 with carbon in natural abundance. They lead to a complete assignment of the carbon resonances of the sugars and bases. In addition, several heteronuclear coupling constants, proton-carbon as well as proton-phosphorous and phosphorous-carbon, were determined. The information can be obtained in a reasonable measuring time and offers valuable information for a detailed picture of DNA structure.